2017
DOI: 10.1038/tp.2017.206
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish, n-3 polyunsaturated fatty acid consumption, and depression risk in Japan: a population-based prospective cohort study

Abstract: Systematic review of observational studies has revealed that fish consumption and levels of n-3 polyunsaturated fatty acids (PUFAs) such as eicosapentaenoic acid (EPA) and docosahexaenoic acid are associated with a reduced risk of depression. A reverse J-shaped effect of n-3 PUFAs was suggested. However, there is limited evidence from populations with high fish consumption and no studies have used a standard psychiatrist-based diagnosis of major depressive disorder (MDD). Therefore, this population-based, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 32 publications
(36 reference statements)
5
78
1
Order By: Relevance
“…Similar to the above cross-sectional data, prospective studies on the relationship between fatty acids and depression show substantial heterogeneity (Lucas et al 2011;Grossoetal.2014;Matsuoka et al 2017). Although other fatty acid classes have also been prospectively studied, most studies again focused on omega-3 fatty acid concentrations or intake.…”
Section: Longitudinal Observational Studiesmentioning
confidence: 80%
“…Similar to the above cross-sectional data, prospective studies on the relationship between fatty acids and depression show substantial heterogeneity (Lucas et al 2011;Grossoetal.2014;Matsuoka et al 2017). Although other fatty acid classes have also been prospectively studied, most studies again focused on omega-3 fatty acid concentrations or intake.…”
Section: Longitudinal Observational Studiesmentioning
confidence: 80%
“…The characteristics of prospective studies included in the meta‐analysis are presented in Table . The smallest sample size was 1181 participants (Matsuoka et al, ), while the largest sample size was 54 632 participants (Lucas et al, ). Of the 10 prospective studies, 4 studies examined the association of both fish and omega‐3 fatty acid intake and depression (Colangelo et al, ; Hakkarainen et al, ; Lucas et al, ; Matsuoka et al, ), 4 studies were focused only on fish consumption (Li et al, ; Mihrshahi et al, ; Smith et al, ; Tsai et al, ), and 2 studies were focused only on omega‐3 fatty acid intake (Kesse‐Guyot et al, ; Persons et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We calculated the RR for 1 serving/week increment of fish consumption and 500 mg/day increment of omega-3 fatty acid intake. For the study that reported results for fish consumption in terms of g/day only (Matsuoka et al, 2017), we supposed that 100 g of fish equals 1 serving as has been done in a previous study of fish consumption (Bouzan et al, 2005;Guevel, Sirot, Volatier, & Leblanc, 2008;Wu et al, 2015). For the analysis of fish consumption, 3 studies were excluded due to insufficient information on the number of cases, number of controls, and exposure categories (Colangelo et al, 2009;Hakkarainen et al, 2004;Lucas et al, 2011), and 3 studies with fewer than 3 exposure categories were also excluded (Mihrshahi et al, 2015;Smith et al, 2014;Tsai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations